Impact of Teachers’ Training on Students’ Learning at Elementary Level - Dr. Asia Khatoon; Dr. Ann Samson; Sobia Ashfaq (Indus Journal of Social Sciences, 2025)
A student’s achievement is a direct result of high-quality teacher preparation. This study was carried out to explore the essential components of teachers’ training programs and how they influence student learning. The research focuses on how teachers’ training influences the academic progress of students at elementary level. The objective of this study was to examine how various elements of teacher training, such as teaching approaches, methods, strategies, content expertise, and classroom management, influence the academic performance and engagement of elementary level students. A student’s performance is an outcome of effective teacher training. This study has been conducted to investigate the relationship between teachers' training and student academic performance. The data has been collected from teachers of shaheed Benazir Abad and Daur.